Food and cigarettes expenses during COVID-19 pandemic on diet quality in Jakarta and surroundings - Rizanna Rosemary; Ratri Ciptaningtyas; Said Usman (AcTion: Aceh Nutrition Journal, 2023)
It is clearly understood that the economic disruption during the COVID-19 outbreak is causing people to lose their income and access to healthy food. Our study aims to investigate people's spending on food and how their daily expenses on cigarettes impact diet quality. We conducted a cross-sectional online survey in April, 2020 and interviews through social media. There were 180 subjects followed in this study. Analysis was conducted using chi-square. It is found that even though our subjects able to access food but their diet quality to have whole food of four food group daily is not adequate. There is significant association between food expenses on whole food and processed food to diet quality (p<0,001). While there is no significant association between smoking behaviours to diet quality (p=0,684) but the percentage of those who smoke 1 to 3 cigarettes and more than 3 cigarettes daily is larger to have poor diet quality rather than people who do not smoke at all. This study concluded household's expenses for cigarettes and food during the COVID-19 pandemic were able to explain whether diet quality is poor or good. The study suggests the government needs to impose smoking restrictions as part of COVID-19 prevention and reassure people's accessibility to nutritious food during this pandemic.